2020
DOI: 10.3390/rel11080425
|View full text |Cite
|
Sign up to set email alerts
|

For Whom the Bell Tolls: Practitioners’ Views on Bell-Ringing Practice in Contemporary Society in New South Wales (Australia)

Abstract: For centuries, religious buildings have been using bells to call the faithful to prayer. Bell-ringing activity on church premises does not serve a purely religious function, however, as people in the community may perceive this activity secularly, attributing their own meanings and significances towards these sounds. If bell ringing (or the actual sound) were found to have great significance to a specific community, denomination, or a regionality bracket, this may have future implications in any management of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…Unlike soundscapes that are a by-product of human activity and thus sensitive to changes in that activity (e.g., aircraft and traffic sounds), church bell ringing creates a soundscape that is directly influenced by purposive human action. We have shown elsewhere the myriad of values imparted by society on church bell ringing in NSW, being both religious and secular in origin ( Parker and Spennemann, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike soundscapes that are a by-product of human activity and thus sensitive to changes in that activity (e.g., aircraft and traffic sounds), church bell ringing creates a soundscape that is directly influenced by purposive human action. We have shown elsewhere the myriad of values imparted by society on church bell ringing in NSW, being both religious and secular in origin ( Parker and Spennemann, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our original study used a mixed methods approach to solicit information pertaining to the presence/nature of church bells, frequency/occasions on which they were rung, augmented with opinions and value judgments regarding bell ringing. While full results of the study are reported elsewhere ( Parker, 2018 ; Parker and Spennemann, 2020 ), we wish to highlight important results from this snapshot of 2018, to make a direct comparison to practices currently occurring due to imposed restrictions as a result of the COVID-19 pandemic.…”
Section: Status Of Church Bell Ringing Pre-covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…and "Is there anything you would like to add about the history of tower bells on your church premises?". Other freeform comments investigated values, perceptions and attitudes of the respondents, but as these data are reported elsewhere [36], we have not included these questions here. See Figure 2 for a flowchart summary of methodological processes.…”
Section: Methodsmentioning
confidence: 99%
“…The authors would like to make the following corrections in relation to the published paper (Parker and Spennemann 2020). The changes are as follows:…”
mentioning
confidence: 99%